CD2 is a surface marker for mouse and rat spermatogonial stem cells - Mito KANATSU-SHINOHARA; Guiying CHEN; Hiroko MORIMOTO; Takashi SHINOHARA (The Society for Reproduction and Development, 2020)
The spermatogonial stem cell (SSC) population in testis is small, and the lack of SSC markers has severely handicapped research on these cells. During our attempt to identify genes involved in SSC aging, we found that CD2 is expressed in cultured SSCs. Flow cytometric analysis and spermatogonial transplantation experiments showed that CD2 is expressed in SSCs from mature adult mouse testes. Cultured SSCs transfected with short hairpin RNAs (shRNAs) against CD2 proliferated poorly and showed an increased frequency of apoptosis. Moreover, functional analysis of transfected cells revealed impairment of SSC activity. Fluorescence activated cell sorting and spermatogonial transplantation experiments showed that CD2 is expressed not only in mouse but also in rat SSCs. The results indicate that CD2 is a novel SSC surface marker conserved between mouse and rat SSCs.